Pengaruh Pendapatan dan Motivasi Kerja Terhadap Kinerja Bidan di UPF Kebidanan Rumah Sakit Umum Prof. Dr. H. Aloei Saboe - Adam, Wirdawaty (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2015)
Health workers are professionals, have characteristics such as developing a unique service to the community, education program, have scientific knowledge, professional duties according to the code of ethics, are free to make decisions in running the profession, received a fee for the services provided, have a professional organization that is constantly improving the quality of service provided to the community. An important aspect to note is the indicator of performance factors midwives in implementing MCH services are influenced by several factors such indicators midwives work motivation and awards received for all the efforts that have been made .. Based on the above it, then the writer interested in studying these problems with title: "The Effect of Income and Work Motivation performance Against Midwifery Midwives in UPF General Hospital Prof. Dr H. Aloei Saboe ".This study aimed to identify the influence of income and work motivation on performance in UPF midwife Midwifery.This type of research is observational study with cross sectional approach Study. The timing of the months January 12 s / d February 12, 2015. The number of samples 65 which is the total sample with independent variable performance midwife while the dependent variable income and work motivation. Processing test data analysis using the chi-square statistic.Result: The distribution is based on income, not fit 38 respondents (58.5%), lack of work motivation 37 respondents (56.9%), while the performance of 35 respondents (53.9%) was driving was measured by using the chi-square formula obtained income effect the performance of the X2 count = 7.82 and the influence on the performance of work motivation count X2 = 18.58; with X2 table, α; 0.05 = 3.48 then the X2 count is greater than X2 table. Conclusion; there penagaruh income and motivation to work on the performance of midwives in UPF Obstetrics General Hospital Prof. Dr.H. Aloei Saboe